Analisis Semiotika Pesan Moral Pada Lirik Lagu “Darurat Judi” Karya Amis - Rosyid, Syafriya Ali; Permadi, Didi; Suparto, Diryo (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The song "Darurat Judi" by Amis is a work that reflects the phenomenon of online gambling that is increasingly widespread in Indonesia, especially among teenagers. This research aims to reveal the meaning behind the lyrics of the song, which not only serves as entertainment but also as a medium to convey a moral message about the dangers of gambling. The method used in this research is a qualitative approach with Roland Barthes' semiotic analysis, which includes the denotative and connotative meanings of the lyrics. The results of the analysis show that the lyrics of this song depict the experience of gambling addiction, regret, and the social and psychological impacts that arise. The conclusion of this study emphasizes that "Darurat Judi" is not just a song, but also a call for social awareness and prevention against the harmful practices of gambling. The message conveyed in this song is relevant to the current social conditions, where online gambling is becoming increasingly accessible and can trap many individuals, especially the younger generation.